Inside Back Cover: A Convergent Total Synthesis of the Telomerase Inhibitor (±)‐γ‐Rubromycin (Angew. Chem. Int. Ed. 17/2014). Issue 17 (1st April 2014) - Wilsdorf, Michael; Reissig, Hans‐Ulrich
<x xml:space="preserve">Abstract</x> Silicon in, silicon out could be the caption for the convergent total synthesis of the telomerase inhibitor (±)‐γ‐rubromycin reported by M. Wilsdorf and H.‐U. Reissig in their Communication on page 4332 ff. They combine three highly functionalized building blocks through selective organometallic chemistry and a silyl‐substituted C3 building block plays a key role. Three acid‐promoted reactions serve to generate the sensitive spiroketal natural product under desilylation. Graphic courtesy of Dr. Daniel Trawney.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>